GUIDELINE FOR THE MANAGEMENT OF BILE DUCT CANCERS BY THE BRAZILIAN GASTROINTESTINAL TUMOR GROUP - RIECHELMANN,Rachel (2016)
ABSTRACT The Brazilian Gastrointestinal Tumor Group developed guidelines for the surgical and clinical management of patients with billiary cancers. The multidisciplinary panel was composed of experts in the field of radiology, medical oncology, surgical oncology, radiotherapy, endoscopy and pathology. The panel utilized the most recent literature to develop a series of evidence-based recommendations on different treatment and diagnostic strategies for cholangiocarcinomas and gallbladder cancers.